Web-based of Payment Information System at Dv Juice and Salad - Apriliana, Sayu Rizky; Aslamiyah, Sulaibatul (Faculty of Economics dan Business, Atma Jaya Makassar University, 2024)
This research aim to design a web-based cashier payment information system that can improve operational efficiency and provide a better service experience to customers at Dv Juice and Salad. The designed cashier payment information system aims to overcome the problem of manual recording that slows down the process and increases the risk of losing records and sales reports. The system was built using the Waterfall method. The advantage of using this method is that it provides a structured framework for managing the system development process as a whole, starting from planning, analysis, design, development, and implementation. The designed cashier information system can record transactions, stock calculations, and generate sales reports automatically, so as to minimise errors and ensure data accuracy. In addition, this system is able to fulfil business needs effectively and efficiently, and can adapt to changes that may occur. Thus, this system not only improves the operational efficiency of Dv Juice and Salad, but also provides a better service experience to customers.